Hong Kong - Fitzpatrick, Liam; Gagliardi, Jason; Stone, Andrew; Gale Group (London Dorling Kindersley Limited, 2015)
Provides travel information on Hong Kong; recommends the 10 best restaurants, bars, hotels, entertainment, and outdoor activities, along with information on trip planning, nightlife, and shopping.
Hong Kong's top 10 -- Around Hong Kong Island -- Around Kowloon -- Around the region -- Streetsmart.
Includes bibliographical references and index.
Keywords: Hong Kong (China) -- Guidebooks